RELATIONSHIPS POWER OF LOCAL ELITE AND VILLAGE HEAD CANDIDATES IN SUKALUYU VILLAGE HEAD ELECTION CONTESTATION SUKAWENING DISTRICT GARUT DISTRICT 2019 - Triyadiansyah, Fikri; Sufajar, Rahmat (Sociae Polites, 2023)
This research focuses on the power relations of the local elite and the village head candidate, namely Asep Kurniawan, where the local elite plays a role and has a stake in the life of Sukaluyu Village, both physically and politically. This study uses elite theory and the concept of power relations which will explain the form of power relations that occur between local elites and Asep Kurniawan and explain the role of local elites in mobilizing community support for Asep Kurniawan in the 2019 Village Head Election in Sukaluyu. This study uses a descriptive method with a qualitative approach. The results of the study show that the power relations that occur between the local elite and Asep Kurniawan are used as a strategic game, domination and governance where each local elite has a political agreement during the Head Election. In addition, this study reveals that the role of local elites in mobilizing community support for Asep Kurniawan has worked well because each local elite has a strong influence with power in each area of Sukaluyu Village, making it easier for Asep Kurniawan to be elected as Head of Sukaluyu Village.